The Obturator Nerve Reflex after Thulium Laser vs. Monopolar Transurethral Resection of Bladder Tumors: A Randomized Clinical trial - Abedi Yarandi, Vahid; Khatami, Fatemeh; Aghamir, Seyed Mohammad Kazem (Urology Journal, 2020)
Purpose: Obturator nerve reflex is the surgery treatment side effect in patients with bladder cancers. This study was run to determine the obturator nerve reflex by Thulium laser versus monopolar Transurethral Resection of Bladder Tumors (TURBT). Materials and methods: After receiving the approval code IRCT20190624043991N4, one hundred and eightynine patients with bladder tumors from 2010 to 2016 were assessed, and among them, 35 patients were randomly assigned into two groups in a blinded manner; the first group (16 patients) received thulium laser and the second group (19 patients) were patients undergoing monopolar transurethral resection of bladder tumor after spinal analgesia. Clinical data, including different variables such as; age, tumor characteristics, gender, operation duration, types of leg jerking, and intraoperative complications, were recorded. The site of the obturator nerve was determined by nerve stimulation, anatomical landmarks, and ultrasonography. Leg jerking was compared in both groups. Results: Of the 35 patients, 28 cases were male, and 7 points were female. The mean ± SD (range) of age was 62.0 ± 6.9 (40-75) years in the Thulium laser group and 64.0 ± 7.1 (41-77) years in the monopolar TURBT group. The mean operation time was not different between the two groups significantly (P > 0.05). Leg jerking was reported in 25% and 63.1% of the patients in Thulium laser and monopolar TURBT groups, respectively (P < 0.05). Conclusion: Thulium laser is a more feasible and effective method to prevent leg jerking in patients with bladder cancer; so, it is recommended more than monopolar Transurethral.